(5u+1)(9+u)=0

Simple and best practice solution for (5u+1)(9+u)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5u+1)(9+u)=0 equation:



(5u+1)(9+u)=0
We add all the numbers together, and all the variables
(5u+1)(u+9)=0
We multiply parentheses ..
(+5u^2+45u+u+9)=0
We get rid of parentheses
5u^2+45u+u+9=0
We add all the numbers together, and all the variables
5u^2+46u+9=0
a = 5; b = 46; c = +9;
Δ = b2-4ac
Δ = 462-4·5·9
Δ = 1936
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$u_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$u_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{1936}=44$
$u_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(46)-44}{2*5}=\frac{-90}{10} =-9 $
$u_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(46)+44}{2*5}=\frac{-2}{10} =-1/5 $

See similar equations:

| 7(1−5x)+3x=36−3x | | 6-6x=6-24x+10 | | x^2-2x-4=2x-1 | | n^2–3n-28=0 | | 2x-9=√3x+9 | | x^2+(x*1.78)^2=10000 | | 9x+12-4x=6x+2 | | X^2+3x-264=0 | | 2x+15=7x−5 | | 3x=180÷6x | | 60°=(x+40) | | 6×-(2x+5)=11 | | (x-5)+25=90 | | 1-3x=x-13 | | (x+2)^2-4=60 | | 5x=x+176 | | y2+3=17 | | .08(60000-y)+.105y=5000 | | -3x-6=1-4x | | 80=32+6x | | 0x+0=-8 | | 154=-4(7+9r)+36r | | t(t-4)(t+7)=0 | | 0(0)+y=-8 | | 95x=3000+10x+.2x^2 | | (x-2)/4-(3x+5)/7=-3,x | | (x-2)/4-(3x+5)/7=-3 | | 4(x-1)+1x=19 | | 4(x+1)-1x=19 | | 5-6r+6r=8 | | 5+4m=64 | | 8-4(y-1)=16 |

Equations solver categories